The Evolution of the Definition and Diagnosis of Barrett Esophagus: A Historical Perspective. Issue 1 (March 2021) - Chandrasoma, Parakrama
Historical definitions of Barrett esophagus (BE) have depended on 2 beliefs: the esophagus is a squamous lined tube and the stomach is a columnar lined sac. Norman Barrett, in 1957, recognized that columnar lining in the tubular esophagus was reflux-induced metaplasia of squamous epithelium, leading to the present definition of BE. Recent evidence that gastric overdistension results in acid exposure of distal esophageal squamous epithelium, causing progressive columnar metaplasia, damage to the lower esophageal sphincter, and dilatation of the abdominal esophagus. This is presently mistaken at endoscopy for proximal stomach. The future definition of BE will likely include intra-sphincteric BE.